Transfigurações contemporâneas: cartografia e pluralidade em Robinson Crusoé - Moraes, Carla Denize (2020)
The current literature and film have the power to resignify the past ones. Imperialism, for centuries, spread eurocentric thought as a way to perpetuate its power, relegating colonized countries to the subaltern position, by the means of spreading negative ou prejudiced images of the colonized people. From the second half of 20th century, there were meaningful changes in the culture and its social actors depiction, in a movement of reflection and questioning about the historical past. The Post-Modernism introduce, therefore, new ways to think about the presente and to look at the past. From this moment, there was a destabilization of the epistemological truths. The Post-Colonialism appears at this context inviting us to reflect about imperialist control, trying to narrate the same histories of the past under new points of view, giving visibility to those who had their culture canceled during centuries of opression. Thus, this work analised a literary and cinematographic corpus which contributes to the realization of the work to resignify the past. The hypotext that motivates the reflections of the post-colonial works is The life and strange surprising adventures of Robinson Crusoe (1719), by Daniel Defoe and its hypertexts are all from the second half of the 20th century. The literary works, in chronological order, are Friday or the other island (1967), by the French Michel Tournier; the Argentinian work Goodbye, Robinson (1984), by Julio Cortázar; and, at last, Foe (1986), by the South-African writer John Maxwell Coetzee. The cinematographic works are two, Man Friday (1975), by the director Jack Gold, and Crusoe (1988), directed by Caleb Deschanel. By these means, we expect we can increase the discussions about Post-colonial literature and cimena, seeking to show that eurocentrism has forged an image from the conquered people in an artificial way, accordin to its interests and, in the moment that it created the subaltern, it also created its own image of superiority. Therefore, our focus was to investigate which was the paths taken by literature and cinema to achieve a transcontextualisation of the premises crystallized by the colonialismo. This investigation was realized by means of bibliographical research, which analysis was guided by the Comparative Literature method. The theory that supports the analysis enlists literature, cinema and culture scholars like Jacques Derrida, Homi Bhabha, Stuart Hall e Ella Shohat, Gayatri Spivak, Robert Stam, Linda Hutcheon, Néstor García Canclini, Silviano Santiago and others. Finally, the work discuss how the recente artistic Productions, theory and critics have been seeking to rethink reality, by the means of questionings and reflections, to achieve a shift in thinking, to recognize the otherness.